Sclerosing Epithelioid Fibrosarcoma of the Bone With Rare EWSR1-CREB3L3 Translocation Driving Upregulation of the PI3K/mTOR Signaling Pathway. (December 2019) - Shenoy, Archana; Surrey, Lea; Jain, Payal; Foster, Jessica; Straka, Joshua; Resnick, Adam; Waanders, Angela; Luo, Minjie; Li, Marilyn; Kazahaya, Ken; Bagatell, Rochelle; Wojcik, John; et al.
Sclerosing epithelioid fibrosarcoma (SEF) is an uncommon neoplasm that rarely presents in bone. It is characterized by epithelioid cells arranged in nests and single-file cords within a sclerotic stromal background which may mimic neoplastic bone. SEF harbors an EWSR1 translocation, which may complicate its distinction from Ewing sarcoma in cases with histomorphologic overlap. We present a diagnostically challenging case of SEF in the mandible of a 16-year-old girl. Our experience highlights the lack of specificity of traditional morphology and EWSR1 break-apart fluorescent in situ hybridization. Open-ended RNA-based fusion gene testing coupled with MUC4 immunohistochemistry aided the eventual diagnosis in this case. Herein, we report the third case of SEF with EWSR1-CREB3L3 translocation and show that this fusion leads to aberrant upregulation of the phosphoinositide 3-kinase/mammalian target of rapamycin signaling pathway in heterologous cell models.